Accurate Training Assistance for Accounting Vocational High School Teachers to Improve the Capability of Computer Accounting Program - Titis Puspitaningrum D.K; Riski Aprilianita (LPPM of NAROTAMA UNIVERSITY, 2019)
Partner problems faced in Accounting Vocational High School Teachers in Surabaya also become a problem for other schools. Learning about accurate is still being a discourse so far and it requires teachers to improve their abilities and knowledge. This makes all high school especially Accounting Vocational High school teachers need to be trained about accurate learning. The purpose of this training is to develop their knowledge related to computers and fulfill the needs of companies who need to use the accurate program. As a result, this program will bring benefit for graduated students so they will easily find a job in the future. To solve this problems, the writer did the assistance on the Subject Teacher Organization (MGMP) Accounting group in Surabaya by providing accurate training. The average results of pre and posttest increases 18.25 points. The result obtained from pre and posttest is very satisfying which 87.5% of teachers received higher point after doing the training. Only one teacher whose point did not change and two teachers whose point decreased and only one teacher whose point decreased into 3